2020
DOI: 10.1016/j.jsurg.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Virtual Reality Tool to Teach Surgical Technique for Tibial Shaft Fracture Intramedullary Nailing

Abstract: Introduction: Active learning methods have accumulated popularity due to improved results in knowledge acquisition as opposed to passive learning methods. For surgical resident physicians with limited training opportunities outside of the operating room due to time constraints, virtual reality (VR) is a relatively inexpensive and time-efficient active training method for procurement of surgical skills. We conducted a simulated intramedullary nailing (IMN) of a tibia to demonstrate VR training programs as a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 20 publications
0
98
0
Order By: Relevance
“…The second most common area of focus was spinal pedicle screw placement (3 out of 16) [ 22 24 ]. Other procedures included tibial shaft fracture fixation [ 25 ], pre-surgery fracture carving [ 26 ], dynamic hip screw placement [ 27 ] and hip arthroplasty [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second most common area of focus was spinal pedicle screw placement (3 out of 16) [ 22 24 ]. Other procedures included tibial shaft fracture fixation [ 25 ], pre-surgery fracture carving [ 26 ], dynamic hip screw placement [ 27 ] and hip arthroplasty [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…ArthroVR was used in 2 articles [ 17 , 18 ], as was insightArthro [ 13 , 16 ]. The remainder of the simulators were used in only 1 article each—Osso VR [ 25 ], Immersive Touch [ 22 ], Procedius [ 14 ], IVRSS-PSP [ 24 ], ORamaVR [ 28 ], VSTS [ 23 ], PrecisionOS [ 15 ], Virtual-Fracture-Carving-Simulator [ 26 ] and TraumaVision [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the reports came from the University of California, Los Angeles David Geffen School of Medicine. 2 The results from the study, which used the Osso VR surgical training platform, showed that VR training improved overall surgical performance by 230% compared with traditional training methods for a tibial shaft surgical procedure. Specifically, surgeons who used the Osso VR platform completed the procedure 20% faster than those not using the platform.…”
mentioning
confidence: 99%